Pemerolehan Bahasa pada Anak Usia Dini - Resi Afuri; Prida Asriani; Rika Afriana; Fatmawati Fatmawati (UIR Press, 2023)
The purpose of this study is to describe language acquisition that occurs in early childhood. The method used is descriptive method with note taking technique. Through this research, the writer can find out and gain knowledge about the language acquisition process that occurs in early childhood. How is the process of mastering the first language as one of the developments that occur in a human being from birth which goes through a very long time since the child does not know a language until the child is fluent in the language. The results of research on language acquisition that occurs in early childhood are that this child has very good language development, he is able to master the words that are around him. The research subjects were also able to say several nouns, verbs and adjectives.